Endobronchial Ultrasound in Evaluating Mediastinal Lymphadenopathy - Baikunje, Nandakishore; Hosmane, Giridhar Belur; Y., Sunil Kumar (Journal of Health and Allied Sciences NU, 2021)
Tuberculosis can involve most of the body parts, and tubercular lymphadenitis is common. But isolated involvement of mediastinal lymph nodes without lung parenchymal involvement is rare in adults. A 45-year-old lady presented with subcarinal lymph node enlargement. A conventional transbronchial needle aspiration done at a local hospital was inconclusive. Endobronchial ultrasound-guided transbronchial needle aspiration was done. Cytology showed epithelioid histiocytes and caseous necrosis. Stain for acid-fast bacilli and cartridge-based nucleic acid amplification test for tuberculosis were positive. Endobronchial ultrasound-guided transbronchial needle aspiration is a minimally invasive bronchoscopic technique to visualize and sample mediastinal lymph nodes. However, its availability is limited to specific centers and expertise is required to interpret images and take diagnostic samples.
Keywords: tuberculosis; mediastinal lymphadenopathy; EBUS-TBNA